Why you need to include human factors in clinical and empirical studies of in vitro point of care devices? Review and future perspectives. (2nd April 2016) - Borsci, Simone; Buckle, Peter; Hanna, George B.
ABSTRACT: Use of in-vitro point of care devices – intended as tests performed out of laboratories and near patient – is increasing in clinical environments. International standards indicate that interaction assessment should not end after the product release, yet human factors methods are frequently not included in clinical and empirical studies of these devices. Whilst the literature confirms some advantages of bed-side tests compared to those in laboratories there is a lack of knowledge of the risks associated with their use. This article provides a review of approaches applied by clinical researchers to model the use of in-vitro testing. Results suggest that only a few studies have explored human factor approaches. Furthermore, when researchers investigated people-device interaction these were predominantly limited to qualitative and not standardised approaches. The methodological failings and limitations of these studies, identified by us, demonstrate the growing need to integrate human factors methods in the medical field.